1981
DOI: 10.1152/jappl.1981.51.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training hypotension: implications for plasma volume, renin, and vasopressin

Abstract: To determine the function of changes in plasma volume (PV), plasma renin activity (PRA), and arginine vasopressin (AVP) in the mechanism of the reduction of resting blood pressure during exercise training, resting supine, sitting, and standing systolic (SBP) and 5th-phase diastolic (DBP) blood pressures were measured in 10 men (19-24 yr) before and after an 8-day (2 h/day) training period on a cycle ergometer. The control group (5 men) exercised at 1.4 1/min [44% peak O2 uptake (VO2 max)] at 23.8 degrees C Tdb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 0 publications
0
20
2
Order By: Relevance
“…For example, patients with idiopathic orthostatic intolerance show a greater decrease in V MCA and a greater increase in CVR compared with age-and sex-matched healthy adults during graded orthostatic stress simulated by head-up tilt (20). The better maintained cerebral perfusion observed in the elderly ACT group compared with the elderly SED cohort in the present study seems to be contrary to the belief that "trained man can run, but they cannot stand" (12). More incidence of orthostatic intolerance in high-fit younger subjects has been observed compared with their age-matched healthy, average-fit counterparts, which has been reportedly related to a greater cardiac compliance (27) that compromises SV output (25) and a diminished baroreflex sensitivity that compromises tachycardiac and vasoconstrictive responses (33).…”
Section: Discussioncontrasting
confidence: 91%
“…For example, patients with idiopathic orthostatic intolerance show a greater decrease in V MCA and a greater increase in CVR compared with age-and sex-matched healthy adults during graded orthostatic stress simulated by head-up tilt (20). The better maintained cerebral perfusion observed in the elderly ACT group compared with the elderly SED cohort in the present study seems to be contrary to the belief that "trained man can run, but they cannot stand" (12). More incidence of orthostatic intolerance in high-fit younger subjects has been observed compared with their age-matched healthy, average-fit counterparts, which has been reportedly related to a greater cardiac compliance (27) that compromises SV output (25) and a diminished baroreflex sensitivity that compromises tachycardiac and vasoconstrictive responses (33).…”
Section: Discussioncontrasting
confidence: 91%
“…Previous studies on the influence of exercise training on orthostatic tolerance reported controversial results, [11][12][13][14]16,28 which may be related to different inclusion criteria, training regimes, methods used for assessment of changes, and a different pathophysiological mechanism, depending on physical capacity: In untrained subjects, symptoms of OI has been related to hypovolemia and a possible cardiac atrophy. 29 In contrast in highly fit subjects, symptoms of OI might be caused by attenuated carotid baroreflex responsiveness and a larger compliance of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Greenleaf et al even stated that "trained men can run, but they cannot stand." 11 Another report indicates that chronic endurance training causes orthostatic hypotension. 12 Smith and Raven suggested that the negative effect of training on orthostatic tolerance was caused by long training periods (Ͼ6 months) at very high levels.…”
mentioning
confidence: 99%
“…The effect of fitness on orthostatic tolerance and syncope remains controversial. A lowered resting orthostatic tolerance has been observed in young highly trained athletes (Levine et al 1991;Raven and Pawelczyk 1993;Ogoh et al 2003), as outlined by the statement ''trained men can run but they cannot stand'' (Greenleaf et al 1981). Others have found orthostatic tolerance to be unchanged (Hernandez et al 2005) or even improved in young highly trained individuals (Convertino 1993;Winker et al 2005).…”
Section: Impact Of Ageing On Vascular Structurementioning
confidence: 99%